THE PERSPECTIVE OF MILLENIALS AND GENERATION Z USERS ON ONLINE INVESTMENT PLATFORMS USING PERSONA APPROACH AND USER JOURNEY - Maulidya, Syafira Nurilhaq; Effendy, Faried; Wuryanto, Eto (Ridwan Institute, 2024)
Millennials and Generation Z, especially those under 30, show strong interest in digital investment but often feel uncertain due to a lack of knowledge and confidence. This study aims to explore their perspective on online investment platforms by focusing on their motivations, goals, obstacles, and needs. The research begins with Desk Research and User Interviews, which are analyzed using Affinity Diagrams to understand these key areas. Based on the findings, a User Persona is created to represent typical users, offering insights into their behaviors and preferences. Additionally, a User Journey is mapped to illustrate users' activities before and after gaining investment experience. The study identifies the ‘Ardian’ Persona, a Millennial who is motivated by the desire to learn, save, and generate additional income. Ardian values safe and user-friendly investment platforms that meet his needs while avoiding potential obstacles. The User Journey reveals that before gaining investment experience, users focus on preparation and self-education, while after gaining experience, they shift their focus to managing investments to achieve their financial goals. This research contributes to UX by providing two key documents: the User Persona and the User Journey. These offer a detailed view of user motivations, challenges, and needs, which can guide the design and improvement of online investment platforms to better serve Millennials and Generation Z users.